A review of intrusion detection system and security threat in internet of things enabled environment - Nisha, Nisha; Gill, Nasib Singh; Gulia, Preeti (Institute of Advanced Engineering and Science, 2024)
Thousands of devices communicate globally to share data and information without any human intervention. A network of physical objects with numerous sensors and other network hardware to exchange data with servers and additional devices that are linked is referred to as the